2014
DOI: 10.1371/journal.pone.0109953
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell Therapy Ameliorates Hyperoxia-Augmented Ventilator-Induced Lung Injury through Suppressing the Src Pathway

Abstract: BackgroundHigh tidal volume (VT) mechanical ventilation (MV) can induce the recruitment of neutrophils, release of inflammatory cytokines and free radicals, and disruption of alveolar epithelial and endothelial barriers. It is proposed to be the triggering factor that initiates ventilator-induced lung injury (VILI) and concomitant hyperoxia further aggravates the progression of VILI. The Src protein tyrosine kinase (PTK) family is one of the most critical families to intracellular signal transduction related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
1
28
1
Order By: Relevance
“…Hyperoxia can damage normal lung tissue and cause neutrophil infiltration, pulmonary edema, destruction of the alveolar epithelial barrier, hyaline membrane formation and interstitial fibrosis [30]. Hyperoxia can also augment ventilator-induced lung injury [31]. However, in the present study, histological changes in the lungs of control rats exposed to a high concentration of oxygen remained constant or showed a slight degree of injury during 24 h of oxygen treatment.…”
Section: Discussioncontrasting
confidence: 64%
“…Hyperoxia can damage normal lung tissue and cause neutrophil infiltration, pulmonary edema, destruction of the alveolar epithelial barrier, hyaline membrane formation and interstitial fibrosis [30]. Hyperoxia can also augment ventilator-induced lung injury [31]. However, in the present study, histological changes in the lungs of control rats exposed to a high concentration of oxygen remained constant or showed a slight degree of injury during 24 h of oxygen treatment.…”
Section: Discussioncontrasting
confidence: 64%
“…Oxidative stress can promote lipid peroxidation to produce MDA [39] and it can also be enhanced by increased NADPH oxidase and MPO [40][41][42]. In this study, we found that Ac2-26 significantly reduced the levels of MDA, NADPH oxidase and MPO activities in the lungs of rats, which were partially attenuated by L-NIO.…”
Section: Ac2-26 Protects Against Lps-induced Apoptosis In Human Alveosupporting
confidence: 50%
“…The biggest hurdle in the study of ESC or iPSC derived lung epithelium is that the resulting cells are immature and do not represent a fully functional differentiated cell. Despite this and other limitations, such differentiation protocols have been used in various models to explore the differentiation potential of human and mouse ESCs and iPSCs including the kidney capsule formation assay (Mou, Zhao et al 2012, Liu, Li et al 2014), lung-on-a-chip type models such as air liquid interface (ALI) culture (Wong, Bear et al 2012, Firth, Dargitz et al 2014), and in bioengineered models such as culture within the decellularized lung (Longmire, Ikonomou et al 2012). The major benefit of patient derived iPSCs is their capacity to harbor genetic mutations that affect respiratory function such as cystic fibrosis or alpha-1 anti-trypsin deficiency.…”
Section: Modeling Lung Disease and Regenerationmentioning
confidence: 99%